Peran Budaya Jawa dalam Pendidikan Anak: Perspektif Ilmu Parenting - Khoiruzzaim Kurniawan (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
This research aims to explore and analyze the role of Javanese culture in the context of children's education, with a focus on the parenting science perspective. Through this approach, this research identifies Javanese cultural values ​​that can make a significant contribution to the child's educational process, as well as detailing how aspects of parenting science can utilize and integrate Javanese cultural heritage to achieve optimal educational goals. This research method involves a qualitative approach with data collection through in-depth interviews, observation and document analysis. Research respondents involved parents, educators and parenting experts who have experience in implementing Javanese cultural values ​​in children's education. Data analysis was carried out using a thematic approach to identify patterns and main findings. It is hoped that the results of this research will provide further understanding of how Javanese cultural values ​​can be integrated with modern parenting principles. It is hoped that the implications of these findings can provide practical guidance for parents, educators and stakeholders in designing educational strategies that are holistic and appropriate to the Javanese cultural context. In addition, it is hoped that this research can contribute to the literature on parenting science and education which focuses on the application of cultural values ​​in supporting children's optimal development.